Analysis of Visual Analog Scale in Measuring the Effect of Spoon Design on the Decision to Buy a Product - Ghia Tri Jayanti; Gina Shobiro Takao; Liandra Khansa Utami; Ligar Muthmainah; Oky Setiawan (Universitas Pendidikan Indonesia (UPI), 2022)
This study was aimed to find the effect of design and material on user behavior and decision making based on image perception with the Visual Analog Scale approach. Cutlery and cooking utensils are almost always owned by households around the world. Spoons have different designs, as in the UK the spoon denotes the culture and habits, eating culture and lifestyle of a particular demographic. Various spoon materials also vary, such as wood, copper, aluminum, zinc, stainless steel, silver to gold. Different treatments that are expressed in the shape, color, style, material, and size of spoons affect the behavior patterns of product users. Small products such as spoons can influence the user's decision-making process. This research uses a quantitative approach to find the effect of design and material on user behavior and decision making based on image perception with the Visual Analog Scale approach. The data in this study were processed using statview software with anova and regression analysis. to see the purchase interest of consumers or users. This study found a correlation between perception and visual taste on product purchase intention influenced by the design and materials used in the product